Making the municipal capital market in nineteenth‐century England. (11th May 2021) - Webster, Ian
Abstract: How did local authorities in nineteenth‐century England raise the money to finance the building of roads, sewers, gasworks, schools, and hospitals? The literature on local government and capital markets is silent on this question. This article reveals the size of the municipal capital market, how and why it developed, and how it performed. It shows that most of the capital came from private individuals and institutions, with central government having only a modest role. Avoiding defaults, protecting lenders, the move towards standardization, and the development of open markets were all important in improving the credibility of borrowers and reducing the cost of debt. The article also reveals that the municipal capital market shared many similarities with the wider capital market.